2012
DOI: 10.1016/j.ajpath.2011.11.015
|View full text |Cite
|
Sign up to set email alerts
|

ALDH1-Bright Epithelial Ovarian Cancer Cells Are Associated with CD44 Expression, Drug Resistance, and Poor Clinical Outcome

Abstract: The role of aldehyde dehydrogenase 1 (ALDH1) as an ovarian cancer stem cell marker and its clinical significance have rarely been explored. We used an Aldefluor assay to isolate ALDH1-bright (ALDH1(br)) cells from epithelial ovarian cancer cell lines and characterized the properties of the stem cells. ALDH1(br) cells were enriched in ES-2 (1.3%), TOV-21G (1.0%), and CP70 (1.2%) cells. Both ALDH1(br) and ALDH1(low) cells repopulated stem cell heterogeneity, formed spheroids, and grew into tumors in immunocompro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
129
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(147 citation statements)
references
References 43 publications
(63 reference statements)
13
129
1
1
Order By: Relevance
“…S2E). Consistent with previous reports (17,22), the cells within such spheroids were enriched for cells that had high levels of ALDH1 expression (Fig. S2F).…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…S2E). Consistent with previous reports (17,22), the cells within such spheroids were enriched for cells that had high levels of ALDH1 expression (Fig. S2F).…”
Section: Resultssupporting
confidence: 79%
“…Compared with ROR1 Low cases, ROR1 Hi ovarian cancers had higher expression of gene signatures associated with the side population, which may contain CSCs (42). Moreover, ROR1 Hi ovarian cancers were enriched for expression of genes associated with embryonic stem cells and EMT (17,25), which facilitates the capacity of tumor cells to migrate and seed metastatic sites (21,43). We also observed that two primary ovarian cancers that expressed ROR1 were better able to grow as xenografts in immune-deficient mice than one that lacked expression of ROR1.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Previous studies showed successful isolation of ovarian CSCs/CICs by the ALDEFLUOR assay. 22 Therefore, the ALDEFLUOR assay is a promising approach to isolate ovarian CSCs/CICs. We next examined the action of fibroblasts on the tumor initiation capacity of CSCs/CICs and the histology of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…aureus is a pathogenic bacterium that is the cause of numerous infections (15). As one of the most important pathogens in orthopaedic infections (16), the treatment of S. aureus is of the utmost importance.…”
Section: Discussionmentioning
confidence: 99%